PENGARUH PEMBERIAN EKSTRAK BAWANG PUTIH (Allium sativum Linn) TERHADAP ZONA HAMBAT PERTUMBUHAN BAKTERI Staphylococcus epidermidis secara in vitro - AKBAR DIOSASQIA PUTRA (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2019)
Background:Infectious diseases are the main cause of high morbidity and mortality rates, especially in developing countries such as Indonesia.Indonesia is abundant with plants that can be used as herbal medicine. Garlic is known as having antibacterial elements, one of them is for Staphylococcus epidermidisÂ  which is one cause of dermal disease. This disease is often ignored in Indonesia because the price of the drug is not affordable by the community. So that garlic should be used as an alternative medicineObjective: This study aims to determine the antibacterial effect of garlic extract (Allium sativum L.) retarding the growth of Staphylococcus epidermidis.Methods: This study is experimental laboratory using plate diffusion method of "Postest Ony Control Group Design" design. There are 7 groups, 5 treatment groups and 2 control groups. The concentration of treatment group was 100%, 50%, 25%, 12,5%, 6,25% while for positive control using chloramphenicol and aquadest as negative control. The bacteria used were Staphylococcus epidermidis.Results: The results showed that garlic extract (Allium sativum L.) had an antibacterial effect in inhibiting the growth of Staphylococcus epidermidis. The inhibitory zone concentration in the statistical results shows there are significant differences with values p = 0.000 or p <Î±.Conclusion: The conclusion of the study showed that Garlic Extract (Allium sativum L.) had an antibacterial effect to retarding the growth of Staphylococcus epidermidis..Keywords: Staphylococcus epidermidis, garlic, antibacteria